Peningkatan Kemampuan Anak Mengenal Huruf Hijaiyah Melalui Flipchard Hijaiyah - Susanti, Desi; Hartati, Sri (Penerbit Aksara Rentaka Siar (ARS), 2019)
The purpose of this research is to improve the ability of the child to know the letter Hijaiyah through flipchard in the PAUD Buah Hati Padang. In order for a child to understand not only the sound of the letter but also the sound each letter Hijaiyah. This type of research is research action class with quantitative methods. Based on the analysis of the data, obtained research results about the improvement of the ability of the child to know the letter Hijaiyah children through the flipcharts that has been implemented in the PAUD Buah Hati Padang success at the end of my cycle I II amounted to 40% but This increase has not reached the minimum completeness criteria (KKM) then this research continues to cycle II. Implementation research in cycle II an increase in the ability of the child to know the letter Hijaiyah significantly through the flipcharts Hijaiyah at the end of the cycle II amounted to 86%. This pictures ability to know the letter Hijaiyah is met.